Community Capacity Building in Developing Rural Tourism Based Suplementer Tourism In Sikka Regency, East Nusa Tenggara Province - Desiderius Siga Meli Poa; Michael Rudolfus Sawu (Cita konsultindo, 2024)
The development of rural tourism is considered highly significant in achieving sustainable development goals. However, to attain this, the capacity building of rural communities is necessary. This research aims to formulate the capacity building of rural communities in the development of rural tourism based on supplementary tourism. The study employs a qualitative method with a qualitative verification approach. Data is collected through observations, interviews, and literature reviews. Informants involved in this research include local communities, tourism practitioners, and local government officials. The collected data is analyzed thematically in a qualitative manner. The research finds that the development of rural tourism products is not yet effective and efficient. The role of stakeholders in the development of rural tourism is also minimal. The implications of this research emphasize the importance of enhancing the capacity of local communities and designing more effective strategies to develop sustainable rural tourism that empowers local communities to access the benefits of rural tourism development.